Crossing the Description - Interpretation Dualism in Phenomenology with Merleau-Ponty - Ali Vahdati Daneshmand; nargess Sajjadieh (روش شناسی علوم انسانی, 2019)
It is commonly accepted that there is a significant difference between the most two prominent readings of phenomenology namely the Husserlian descriptive and Heideggerian interpretive ones. The present paper probes first to show that the aforementioned distinction arises from limited examination of Husserl's works. Besides, it is reflected that genetic themes with more hermeneutical elements in his last phase of thought have been neglected in the literature of the field. Second, a new approach is proposed, with the help of Merleu-ponty’s phenomenology, which in spite of similarities with both readings, goes beyond them. This new approach consists of three fundamental insights: (Re) considering the world, operative intentionality against thematized intentionality and considering passive synthesis at the final stage. Accordingly, some methodical suggestions include restricted and operative Epoche, description, imaginative variation, passive return to the phenomenon, and ongoing validation of the explanatione